PRELIMINARY APPRAISAL OF THE PRAWN FISHERY OF KERALA - Banerji, S K; Chakraborti, D (Indian Journal of Fisheries, 2011)
A preliminary appraisal of the relation between fishing effort and catch of prawnsin the Kerala waters has been made, using the prawn catch data available with the CentralMarine Fisheries Research Institute and of the medium-sized vessels of the Governmentof India and the Indo-Norwegian Project operating along the Kerala coast from1957 to 1969. The decline in catch per unit effort and the decline in the mean size ofprawns in the commercial catches of Kerala are not signs of over-fishing but are indicationsof an expanding fishery. The analysis shows that very little increase in the catchwill result even when the fishing effort is increased substantially and the immediateneed is to stabilise the production at its present level.